(untitled) (Architecture Image Studies, 2026)
This study examines how sport governance contributes to improving regional athletic performance through a case study of Lamongan Regency. Employing a qualitative case-study design, data were collected through in-depth interviews, policy document analysis, and limited observation, and were analyzed using Creswell’s qualitative analysis procedures. The analytical framework draws on Henry and Lee’s sport governance model—systemic governance, organizational governance, and political governance—engaged in dialogue with contemporary governance and public administration scholarship. The findings indicate that regional sport performance is shaped by the simultaneous interaction of these three governance dimensions. The study shows that weak cross-sectoral integration, particularly between sport and education, constrains the effectiveness of systemic governance; unequal internal participation undermines organizational governance; and misaligned political commitments among key actors impede the translation of political support into performance outcomes. The study’s novelty lies in advancing the concept of performance-oriented sport governance at the subnational level, emphasizing cross-sectoral integration, balanced organizational participation, and aligned political governance as prerequisites for sustaining performance improvements. This study contributes to public administration and sport governance research and offers policy implications for strengthening subnational sport governance.